The role of law in global value chains: a research manifesto - Grietje Baars; Jennifer Bair; Liam Campling; Dan Danielsen; Dennis Davis; Klaas Hendrik Eller; Dez Farkas; Tomaso Ferrando; Jason Jackson; David Hansen-Miller; Elizabeth Havice; Claire Mummé; et al. (Oxford University Press, 2022)
Most scholars attribute the development and ubiquity of global value chains to economic forces, treating law as an exogenous factor, if at all. By contrast, we assert the centrality of legal regimes and private ordering mechanisms to the creation, structure, geography, distributive effects and governance of Global Value Chains (GVCs), and thereby seek to establish the study of law and GVCs as rich and important terrain for research in its own right.